Altered gene expression in hippocampus and depressive-like behavior in young adult female mice by early protein malnutrition - Belluscio, Laura María (2016)
Perinatal development represents a critical period in the life of an individual. A common cause of poor development is that which comes from undernutrition or malnutrition. In particular, protein deprivation during development has been shown to have deep deleterious effects on brain's growth and plasticity. Early-life stress has also been linked with an increased risk to develop different psychopathologies later in life. We have previously shown that perinatal protein malnutrition in mice leads to the appearance of anxiety-related behaviors in the adulthood. We also found evidence that the female offspring was more susceptible to the development of depression-related behaviors. In the present work, we further investigated this behavior together with its molecular bases. We focused our study on the hippocampus, as it is a structure involved in coping with stressful situations. We found an increase in immobility time in the forced swimming test in perinatally malnourished females, and an alteration in the expression of genes related with neuroplasticity, early growth response 1, calcineurin and c-fos. We also found that perinatal malnutrition causes a reduction in the number of neurons in the hippocampus. This reduction, together with altered gene expression, could be related to the increment in immobility time observed in the forced swimming test.